Kidney grafts from donors ≤5 yr of age: Single kidney transplantation for pediatric recipients or en bloc transplantation for adults?. (26th February 2013) - Gallinat, Anja; Sotiropoulos, Georgios C.; Witzke, Oliver; Treckmann, Jürgen W.; Molmenti, Ernesto P.; Paul, Andreas; Vester, Udo
Abstract Kidneys from donors ≤5 yr of age represent a controversial issue. The purpose of this study was to compare the transplant outcomes as single and single/en bloc grafts into pediatric and adult KT recipients, respectively. All recipients of kidneys from donors ≤5 yr old transplanted at our institution from 3/2003 to 12/2010 were evaluated, and corresponding data were analyzed. There were 11 pediatric and 14 adult recipients. Median donor age and body weight were 38 months and 14 kg, respectively. PNF, n = 2 and DGF, n = 1 were observed only among adult recipients. Five‐yr graft survival was 100% for children and 86% for adults. There were no significant differences in graft and patient survival, PNF, DGF, acute rejection, or postoperative complications among children/single (n = 10), adults/en bloc (n = 10), and adults/single (n = 4) KT. Major complications were documented in six adult recipients and one pediatric recipient after en bloc KT. Pediatric recipients showed significantly higher GFR during the first post‐transplant year. Kidneys from donors ≤5 yr of age have at least as good outcomes as when transplanted as single allografts into children. Although the study‐volume is small, it seems that children benefit from a pediatric‐oriented allocation policy.